Patients' and family caregivers' experiences and perceptions about factors hampering or facilitating patient empowerment for self-management of hypertension and diabetes in Cameroon - Amélie Mogueo; Barthelemy Kuate Defo (BMC, 2022)
Abstract Background Noncommunicable diseases like hypertension and diabetes require long-term management, and are financially draining for patients and their families bearing the treatment costs, especially in settings where the inadequacy or non-existence of the health insurance system prevails. Patient empowerment-focused interventions have been shown to improve adherence to therapeutic regimens and decrease unnecessary health care utilization and costs. This study aims to examine enabling and impeding factors to the development of patient empowerment in a resource-limited setting like Cameroon. Methods We used qualitative methods entailing three levels of investigation and involving a public primary healthcare hospital in Yaoundé, Cameroon. Data were collected through 40 semi-structural interviews with patients having hypertension or diabetes and their family caregivers, one focus group discussion with six patients, 29 observations of consultations of patients by specialist physicians, seven observations of care received by inpatients from generalist physicians, and nine documents on the management of hypertension or diabetes. A novel approach combining thematic and lexicometric analyses was used to identify similarities and differences in barriers and facilitators associated with patient empowerment at different levels of the healthcare delivery system in Cameroon. Results Barriers generally outnumbered facilitators. There were particularities as well as commonalities in reported facilitators and barriers linked to patient empowerment from different experiences and perspectives of outpatients, inpatients and their family caregivers, given the healthcare services and organization of health personal and resources that deliver healthcare services to meet the health needs of patients with hypertension or diabetes in Cameroon. While specific factors identified by patients were directly related to the self-management of their disease at the individual level, family caregivers were mainly focused on factors present at organizational and central levels, which are indirectly related to the management of the diseases and beyond the control of patients and families. Conclusions The preponderance of individual-level factors linked to patient empowerment more than those at the central and hospital/organizational levels calls for due attention to them in the multilevel design and implementation of patient empowerment interventions in resource-limited settings like Cameroon. Accounting for patient's and families' perspectives and opinions may be key to improving healthcare delivery.